Perencanaan Instalasi Solar Home System (SHS) Untuk Kapasitas Daya Listrik Rumah 2.200 VA - Andi, Kms.; Riyana, Andri; Pratama, Verga Wido (Jurnal Ilmu Siber dan Teknologi Digital, 2024)
Purpose: This study aims to design an off-grid Solar Home System (SHS) to meet the daily electricity needs of a household with a 2,200 VA power capacity in Indonesia. The goal is to utilize Indonesia’s abundant solar energy potential to accelerate electrification and reduce its dependence on fossil fuels. Methodology/approach: This method involves identifying the household’s daily electrical load, which totals 16,325 Wh, including LED lights, refrigerators, air conditioners, and various other electronic devices. Based on this demand, the SHS system was designed using 20 solar panels of 200 Wp each (total 4,000 Wp), seven 12V 200Ah batteries (total storage of approximately 16,800 Wh), a 120A solar charge controller, and a 2,000W inverter. The design ensures that the system operates independently, without a connection to the national grid. Results/findings: The results show that the designed SHS can reliably supply the daily household electricity needs by storing sufficient energy for nighttime or cloudy conditions. This demonstrates that a household-scale solar power system is feasible and sustainable in a region with high solar radiation, such as Indonesia. Conclusion: The study concluded that SHS is an effective solution for residential electricity needs and supports the transition to renewable energy. However, the limitations include the lack of seasonal solar data analysis and economic feasibility assessment. The backup system design is also not considered. Limitations: Despite these limitations, the study contributes as a technical reference for SHS planning, supporting energy access initiatives, and clean energy adoption in remote or underserved areas. Contribution: This study provides a practical design reference for off-grid solar power systems in typical Indonesian households. It supports renewable energy adoption and rural electrification and encourages decentralized energy solutions using locally available solar resources.